PENGARUH PROMOSI DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA APLIKASI E-COMMERCE TOKOPEDIA - Andiani, Lidia; Riantama, Farrel; Andriansyah, Agussalim (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2023)
The purpose of this study was to test the Promotion (X1) and Consumer Trust (X2) variables on Purchase Decisions (Y) in the Tokopedia E-Commerce application in the Management student study program at STIE Malangkucecwara in the 2022/2023 academic year. The type of research used in this research is quantitative research with explanatory methods. The population of this study was 163 students with a sample of 62 students. The analytical method used in this study used the IBM SPSS Statistics 23 application. The results showed that the Promotion variable (X1) had a positive effect of 5,600 and the Consumer Trust Variable (X2) had a positive effect of 4,218. From the results of this study, it can be concluded that Promotion and Consumer Trust influence purchasing decisions.